E-MONITORING PERFORMANCE LECTURER BASED ON CLOUD COMPUTING SYSTEM - Suparmin Suparmin; Dianna Ratnawati; Samsul Hadi (VANOS Journal of Mechanical Engineering Education, 2019)
Lecturers in study programs make a major contribution to the quality of study program accreditation, particularly in the upcoming IAPS 4.0 completeness. The lecturer base needs to be managed through a concrete, transparent, structured, comprehensive, and accountable system. Lack of data management in lecturers at the Mechanical Engineering Education / PTM Study Program so far is still paperless based so that it is less effective, efficient, having to copy documents, and tends only to collect data close to the accreditation of study programs. This research aims: (1) to produce e-monitoring products on the performance of lecturers based on a cloud computing system; (2) knowing the level of feasibility of e-monitoring products on the performance of lecturers based on cloud computing system at PTM Study Program. The research method uses Research and Development (R&D), which adopts the ADDIE (Analysis-Design-Development-Implementation-Evaluation) model. The research sample was 11 PTM lecturers. Validators of eligibility included the chairman of the LPM and the chair of the UST IT team. The instruments used included questionnaires and documentation. This research succeeded in producing a product in the form of a cloud computing system with a private cloud type with the Platform As A Service (PaaS) model. The data used as an assessment of lecturer performance include governance, HR performance, education performance, research performance, and service performance. The results of expert assessments obtained an average of 91.25%, which shows that this system is very feasible to use. While the evaluation results of the system implementation showed that 90% of PTTM lecturers were able to understand and skillfully operate the cloud system, thus this system is very feasible to be used as e-monitoring of lecturer performance that is accurate, accountable, objective, and safe to use.